Les stèles de l'an 3 d'Aspelta - Valbelle, Dominique, (Bibliotheque d'Etude ;, 2012)
"A new stele dated Year III of Aspelta was discovered one fragment after another between 1999 and 2007 on the site of Dukki Gel (Pnubs), one kilometre north of Kerma. What started as archaeological research turned into a police investigation when the largest fragment was confiscated from a Sudanese man who had sent a copy of the text to the Museum of Khartoum to enquire about the potential commercial value of the object in his possession. Five fragments constituting the main part of the upper and median sections of the stele could thus be reassembled, along with two fragments of the lower rim. The scarce number of Napatean inscribed monuments known to us makes every new discover likely to shed entirely new light on this very specific period when the Kushite kings ceased to rule over Egypt but kept close cultural relationships with it beyond the now interrupted political links. The date of the stele - Year III, 1st month of Winter, the 12th - places it twenty days after the stele from Sanam, downstream of the 4th cataract, now in the Louvre Museum (C 250 = E 6209) which is dated Year III, 3rd month of the akhet season, the 22nd day. The latter commemorated the visit to the temple of Amun-Ra Bull of Nubia by a delegation sent by the king to replace the sistrum player of the temple. Reading the inscription of stele from Dukki Gel shows that most members of the delegation of the Sanam stele are still mentioned here, although important redactional discrepancies are to found between the two texts. A comparison of the two inscriptions lets us establish certain orthographic rules followed by the scribe of each stele, one with an Egyptian training while the other one seems to have been influenced by a specific local culture, which the Dukki Gel stele contributes to reveal." -- Page 4 of cover.